2011
DOI: 10.1182/blood-2010-09-305664
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-inhibitory factor 1 dysregulation of the bone marrow niche exhausts hematopoietic stem cells

Abstract: The role of Wnt signaling in hematopoietic stem cell fate decisions remains controversial. We elected to dysregulate Wnt signaling from the perspective of the stem cell niche by expressing the pan Wnt inhibitor, Wnt inhibitory factor 1 (Wif1), specifically in osteoblasts. Here we report that osteoblastic Wif1 overexpression disrupts stem cell quiescence, leading to a loss of self-renewal potential. Primitive stem and progenitor populations were more proliferative and elevated in bone marrow and spleen, manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 50 publications
0
56
1
Order By: Relevance
“…HSCs lacking both Tcf1 and Lef1 were able to successfully repopulate all non-T blood lineages in primary and secondary hosts, but their capacity for blood regeneration was compromised in the tertiary hosts. This functional deficiency remarkably resembles that observed in transgenic expression of Wnt inhibitors such as Dkk1 and Wif1 and in Wnt3a-deficient fetal liver cells (11)(12)(13). In those studies where Wnt activity is manipulated, a general concern is that such intervention has a side effect on bone structure and/or stromal cells and thus may have altered HSC niches.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…HSCs lacking both Tcf1 and Lef1 were able to successfully repopulate all non-T blood lineages in primary and secondary hosts, but their capacity for blood regeneration was compromised in the tertiary hosts. This functional deficiency remarkably resembles that observed in transgenic expression of Wnt inhibitors such as Dkk1 and Wif1 and in Wnt3a-deficient fetal liver cells (11)(12)(13). In those studies where Wnt activity is manipulated, a general concern is that such intervention has a side effect on bone structure and/or stromal cells and thus may have altered HSC niches.…”
Section: Discussionmentioning
confidence: 67%
“…Overexpression of Dkk1 or Wif1, which blocks the interaction between Wnt ligands and their receptors, diminishes HSC quiescence and its repopulation capacity (11,12). Wnt3a deficiency also greatly impaired HSC activity (13).…”
mentioning
confidence: 99%
“…In class I MHC Ϫ/Ϫ mice, the anabolic PTH/bone effect was abrogated, highlighting the importance of T cells in trabecular bone formation (126). Furthermore, it is acknowledged that osteoblast-specific overexpression of the Wnt inhibitor DKK1 or WIF caused an impaired HSC self-renewal (26,104). These findings revealed tantalizing scenarios regarding the involvement of different niches controlling PTH effects on trabecular bone resorption/formation and on HSC homing.…”
Section: Pth Outcomes: Exploring "The Bright and The Dark Side Of Thementioning
confidence: 99%
“…1 A lthough the introduction of reducedintensity conditioning (RIC) has decreased treatment-related mortality associated with myeloablative conditioning, it is currently being actively debated whether patients should be treated with RIC allogeneic stem cell transplantation (RIC alloSCT) with its substantial morbidity and risk of mortality as part of first-line therapy, even if a late survival benefit can be demonstrated. A recent consensus report on alloSCT in MM concluded that new strategies are needed to improve the…”
Section: Philippe Moreau University Hospital Nantesmentioning
confidence: 99%
“…1 H ematopoietic stem cells give rise to our entire blood cell repertoire throughout adult life, and hence the balance of selfrenewal and differentiation of HSCs needs to be tightly controlled. Intrinsic signals and signals from the HSC niche microenvironment, including osteoblasts, are key to maintaining this balance.…”
mentioning
confidence: 99%